APLIKASI PENJUALAN DAN PEMBELIAN PADA APOTEK ROSA DELIMA KENDARI BERBASIS PEMROGRAMAN DELPHI 7 - Remilton Gerardus Narang; Alfin Thomas (Simtek : jurnal sistem informasi dan teknik komputer, 2020)
The purpose of this study, to design a sales information system and drug purchasing at Rosa Delima Pharmacy which is useful in managing the sales, purchasing and reporting system quickly and accurately, which is now still doing the sales, purchasing and reporting system manually, in other words still doing data processing by recording regular notes. The impact that can be felt from this designed system is the ease in managing the business of selling goods, especially for the owner of Rosa Delima Pharmacy itself, the method used in designing this system is the DFD design method, the database design method uses ER and the programming language used is the programming language Delphi. The results of this study are an Application of Sales and Purchases at Rosa Delima Pharmacy Kendari